Obesity and the Risk of Intubation or Death in Patients With Coronavirus Disease 2019. Issue 11 (November 2020) - Frank, Rachel C.; Mendez, Sean R.; Stevenson, Elizabeth K.; Guseh, James S.; Chung, Mabel; Silverman, Michael G.
Abstract : Objectives: To characterize the impact of obesity on disease severity in patients with coronavirus disease 2019. Design: This was a retrospective cohort study designed to evaluate the association between body mass index and risk of severe disease in patients with coronavirus disease 2019. Data were abstracted from the electronic health record. The primary endpoint was a composite of intubation or death. Setting: Two hospitals in Massachusetts (one quaternary referral center and one affiliated community hospital). Patients: Consecutive patients hospitalized with confirmed coronavirus disease 2019 admitted between March 13, 2020, and April 3, 2020. Interventions: None. Measurements and Main Results: A total of 305 patients were included in this study. We stratified patients by body mass index category: < 25 kg/m 2 (54 patients, 18%), ≥ 25 kg/m 2 to < 30 kg/m 2 (124 patients, 41%), ≥ 30 kg/m 2 to < 35 kg/m 2 (58 patients, 19%), and ≥ 35 kg/m 2 (69 patients, 23%). In total, 128 patients (42%) had a primary endpoint (119 patients [39%] were intubated and nine died [3%] without intubation). Sixty-five patients (51%) with body mass index greater than or equal to 30 kg/m 2 were intubated or died. Adjusted Cox models demonstrated that body mass index greater than or equal to 30 kg/m 2 was associated with a 2.3-fold increased risk of intubation or death (95% CI, 1.2–4.3) compared with individuals with body mass index less than 25 kg/m 2 . Diabetes was also independently associated with risk of intubation or death (hazard ratio, 1.8; 95% CI, 1.2–2.7). Fifty-six out of 127 patients (44%) with body mass index greater than or equal to 30 kg/m 2 had diabetes, and the combination of both diabetes and body mass index greater than or equal to 30 kg/m 2 was associated with a 4.5-fold increased risk of intubation or death (95% CI, 2.0–10.2) compared with patients without diabetes and body mass index less than 25 kg/m 2 . Conclusions: Among consecutive patients hospitalized with coronavirus disease 2019, obesity was an independent risk factor for intubation or death.